The Relationships Between Web 2.0 Tools, Cooperative Learning And Higher Order Thinking Among King Saud University Students - Mohammed S, Alblehai Fahad (2017)
The aim of providing a sustainable learning environment for sharing knowledge has become the main priority of higher education in Saudi Arabia. In Saudi universities, teaching is mostly conducted based on a teacher-centered method, which deprives students of the opportunity to communicate with their instructors or create their own group. This situation, in turn, is believed to affect the students‘ learning characteristics toward the course. Instructors in different Saudi universities hope to have a more precise and efficient understanding of the effects of Web 2.0 tools on the development of students‘ higher-order thinking skills and group cooperative learning activities.